(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: It is critical to offer evidence-based practice (EBP) programs to undergraduate nursing students. Evidence- based nursing practice is essential for improving patient care, increasing clinical judgment, and encouraging professional development. Future nursing practices greatly depend on what nursing students think and are willing to do with EBNP. But a lack of knowledge and other implementation barriers may impact their preparedness and use in clinical settings. Objective: The objective of this study was to assess nursing student belief and willingness to implement evidence-based nursing practice. Methodology: A straightforward study was done with 141 nursing students using a set questionnaire that included the evidence-based practice belief (EBPB) scale and evidence-based practice implementation (EBPI) scale. Data were analyzed using SPSS version 23, including frequencies and percentages, to summarize the data. Results: The study was conducted on a total sample of 141 participants, including 71 third-year students and 70 fourth-year students, and revealed around 62.41% knew the meaning of EBP. Only 36.17% had received training related to the EBP. Encouragingly, 86.52% of research participants were willing to apply evidence-based practice nursing. The study showed that more than 50% of students held positive beliefs about EBPN and low implementation in their clinical. Conclusion: There is a big difference between what nursing students believe and how willing or able they are to use EBNP in clinical settings. To overcome this gap and improve nursing practice in the future, it is suggested that educational methods like curriculum integration, mentor ship, workshops, and better access to evidence-based resources be used.